Drugs to limit Zika virus infection and implication for maternal-fetal health - Kumar, Ankur; Kumar, Deepak; Jose, Joyce; Giri, Rajanish; Mysorekar, Indira U. (Frontiers in Virology, 2022)
Although the placenta has robust defense mechanisms that protect the fetus from a viral infection, some viruses can manipulate or evade these mechanisms and disrupt physiology or cross the placental barrier. It is well established that the Zika virus is capable of vertical transmission from mother to fetus and can cause malformation of the fetal central nervous system (i.e., microcephaly), as well as Guillain-Barre syndrome in adults. This review seeks to gather and assess the contributions of translational research associated with Zika virus infection, including maternal-fetal vertical transmission of the virus. Nearly 200 inhibitors that have been evaluated in vivo and/or in vitro for their therapeutic properties against the Zika virus are summarized in this review . We also review the status of current vaccine candidates. Our main objective is to provide clinically relevant information that can guide future research directions and strategies for optimized treatment and preventive care of infections caused by Zika virus or similar pathogens.